Formation of political organizations in Western Siberia during fragmentation and collapse of CPSU. 1989–1991 - S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
The events of the 1980s, perestroika in the USSR and the rapid process of politicization of relations between social groups, require further analysis. The actual material accumulated and processed in a series of dissertations and monographic West Siberian studies makes it possible to analyze the contribution of political forces that appeared during the years of perestroika to the destruction of the administrativecommand system for a long time ensuring the existence and development of the Soviet state. Even after 30 years, it is difficult to determine what these events were: the counter-revolution, the revolution, the Thermidorian upheaval.This situation is complicated by the differences in the interests of the political forces that took part in the collapse of the Soviet system of government, as well as a change in the attitude of the participants in the events themselves to their past experience